Mothers’ Behaviour and Barriers in Early Childhood Sexuality Education in Central Java - Meilani, Niken; Wibowo, Queenaisya Elfaiza; Retnaningsih, Yuliantisari (Universitas Airlangga, 2026)
Background: Child sexual abuse (CSA) is a major global public health concern, affecting 18% of girls and 7.6% of boys worldwide. In Indonesia, over 14,000 cases were reported in 2022, underscoring the urgency of preventive action. Early sexuality education effectively reduces CSA risk; however, its implementation is limited by cultural taboos, parental discomfort, and inadequate communication skills. Mothers play a vital role in teaching body safety and personal boundaries, but related behaviors and influencing factors are underexplored in Indonesia. Objective: To examine mothers’ behaviors in providing sexuality education to young children and identify the influencing factors and barriers. Methods: A descriptive-analytical survey was conducted among 42 mothers of kindergarten students in Sawangan District, Magelang, from January to March 2025. Mothers’ behavior in delivering sexuality education served as the dependent variable, while independent variables included intention, self-efficacy, attitude, perception, communication barriers, and husband’s support. Data were collected using validated questionnaires and analyzed using descriptive statistics and path analysis. Results: Mothers mainly discussed topics related to family roles, boundaries, and hygiene, but rarely covered pregnancy or childbirth. The analysis showed that intention influenced behavior (β = 0.486, p = 0.000), and was predicted by self-efficacy (β = 0.714, p = 0.000). Self-efficacy was shaped by barriers, perception, and attitude, while husband’s support helped reduce barriers. Conclusion: Enhancing mothers’ self-efficacy, addressing cultural barriers, and involving fathers can strengthen the delivery of sexuality education. This study advances understanding of parental determinants in CSA prevention within Indonesia’s cultural context.